2018
DOI: 10.1111/iju.13755
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo stone surgery in donor kidneys at renal transplantation

Abstract: Our experience suggests that both ex vivo ureteroscopy and ex vivo pyelolithotomy procedures can safely and effectively be carried out in stone-bearing living donor kidneys, without compromising renal allograft function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
(56 reference statements)
0
9
0
6
Order By: Relevance
“…The main advantage of CT is that precontrast imaging enables the detection of asymptomatic kidney stones. Donor kidney stones are known to be a relative contraindication for transplantation [9]. Ultrasonography has a low sensitivity, especially in the detection of kidney stones <5 mm, and noncontrast CT is currently the gold standard for visualizing stones of this size [10].…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of CT is that precontrast imaging enables the detection of asymptomatic kidney stones. Donor kidney stones are known to be a relative contraindication for transplantation [9]. Ultrasonography has a low sensitivity, especially in the detection of kidney stones <5 mm, and noncontrast CT is currently the gold standard for visualizing stones of this size [10].…”
Section: Discussionmentioning
confidence: 99%
“…The stonefree rates of ex vivo stone surgery reported in the literature range between 89.5 and 100% [45,46]. A recently published series of 13 donors with 4-15 mm stones who underwent ex vivo ureteroscopy (n = 6) or ex vivo pyelolithotomy (n = 7) further demonstrated the safety and efficacy of both procedures in live donor kidney transplantation [47]. The authors recommended ex vivo ureteroscopy as the first choice because it is easy to perform and has a low risk for morbidity, and they also recommended using a pediatric cystoscope for the procedure because it allows better handling and maneuvering.…”
Section: Allograft Urolithiasismentioning
confidence: 99%
“…An urgent problem and challenge for organ transplant physicians is how to maximize the use of organs available for transplantation. Many transplant centers have reported success using a kidney with stones as a donor kidney, and all have achieved good results (5,6). A previous study has shown that minimally invasive treatment of kidney stones in vitro can minimize the damage to the donor kidney, and donor kidney stones are no longer an absolute contraindication for kidney transplantation (7).…”
Section: B C Amentioning
confidence: 99%